Respuestas

2013-11-09T12:02:43+01:00

9x + 16y = 7        (1)
- 3x + 4y = 0        (2)

de (1)
          9x = 7 - 16y
            x = (7 - 16y)/9       (3)
(3) en (2)
         - 3(7 - 16y)/9 + 4y = 0
         - (7 - 16y)/3 + 4y = 0
          - 21 + 16y + 12y = 0
                     28y = 21
                                         y = 21/28
En (2)
            - 3x + 4(21/28) = 0
                      - 3x + 3 = 0
                                         x = 1
Solución del sistema
                x = 1
                y = 21/28